PENGARUH PRODUK PLACEMENT MEREK CITRA PADA FILM SURGA YANG TAK DIRINDUKAN TERHADAP KEPUTUSAN PEMBELIAN - Yuliana Sari; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The mass media is a place to perform activities of marketing communications. One of them on electronic media, namely television advertising. Product placement became the choice of a new marketing and is considered influential and effective. SOR Theory explain how stimuli can get by organism and get some respons from that. Product placemet is brand placement conducted between scenes on the sidelines of films, television programs and other media, so the audience cannot avoid such as avoiding television commercials. This study uses a quantitative research methods ekplanatif. The data collection is done by distributing questionnaires to 96 respondents Riau University student who had been watching surga yang tak dirindukan film. and citra’s product users. Analysis of data using simple linear regression in SPSS 20 for windows.The results showed that the influence of product placement citra’s product on Surga yang Tak Di Rindukan Films on purchasing decisions, Y = 18.784 + 0.721 X. number constants (a ) of 18.784 and purchase decisions variable coefficient of 0.721 . while t 6.911 is greater than t table 3,394. with a significance level of 0.000 is smaller than a = 0:05. and " Model Summary " shows that the value of R = 0580 and the coefficient of determination ( R_square ) is equal to 0.337. it means that the contribution of the influence of product placement Citra’s product on Surga yang Tak di Rindukan film. the purchasing decision is at 33.7 % with a weak category, the rest is influenced by other factors not examined in this study. Keywords : Marketing Communications, Advertising, Product Placement, Purchase Decisions